The application of hierarchy MoS2 particles for NIR induced drug delivery towards liver cancer treatment. (28th October 2020) - Wang, Kai; Li, Chengfang; Li, Yin; Wang, Jinjing; Ma, Aiqing
Abstract: This paper applied hierarchy MoS2 particles for near-infrared induced drug delivery towards liver cancer treatment. MoS2 particles were used as the photothermal responsive agent, 1-tetradecanol was used as the phase change material, doxorubicin was encapsulated into the particles, and MoS2 /1-tetradecanol@doxorubicin composite was synthesized. The drug release was tested under near-infrared irradiation. Within the MoS2 /1-tetradecanol@doxorubicin composite, the photothermal response of MoS2 to near-infrared facilitated the phase change of 1-tetradecanol and the release of doxorubicin. The release of doxorubicin could be regulated by both the MoS2 concentration and the irradiation power. The cytotoxicity study indicated that MoS2 /1-tetradecanol had negligible toxicity to the HepG2 cells, while MoS2 /1-tetradecanol@doxorubicin had more tumor-killing effects than free doxorubicin. This research showed that hierarchy MoS2 particles had the potential of delivering anti-tumor drugs through photothermal stimuli.